Impact of lymphadenectomy rates in the quality assurance program in early ovarian cancer of the AGO Study Group: real-world observations - Wimberger, Pauline; Pfisterer, Jacobus; du Bois, Andreas; Hilpert, Felix; Kerkmann, Markus; Sehouli, Jalid; Mahner, Sven; de Gregorio, Nikolaus; Hanker, Lars; Heitz, Florian; Marmé, Frederik; Wölber, Linn; et al. (European journal of surgical oncology, 2025)
Objectives - The German quality assurance program (QS-Ovar) representatively documents treatment and survival for patients with the initial diagnosis of primary ovarian cancer in the third quarters of 2004, 2008, 2012, 2016, and 2021. We evaluate lymphadenectomy (LNE) rates in dependence on histologic subtype and outcome for early ovarian cancer FIGO I. - Methods - Therapy quality was defined according to national guidelines. Surgical quality was categorized as “optimal“ (SUR+: maximum 1 surgical item missing), versus “suboptimal“ (SUR-); analogous categorization “optimal“ systemic treatment (CT+) and “suboptimal“ (CT-). - Results - Overall, 832 pts. (19.3 %) were diagnosed with FIGO I, of them 47.6 % with FIGO IC, 35.7 % had a high-grade serous subtype, 5.0 % low-grade serous, 6.9 % low-grade endometrioid, 18 % high-grade endometrioid, 11 % clear cell, and 18 % mucinous tumors. The optimal surgical standard increased from 21.1 % (2004) to 53.0 % (2012). Surgical quality has remained unchanged in 2021 with 53.8 % and SUR + -subgroup with 74.2 %. The rate of pelvic and para-aortic lymphadenectomy increased over time for high-grade serous and clear cell carcinoma and decreased for mucinous carcinoma. In 2021, 67.6 % had ≥25 resected lymph-nodes in high-grade serous, 46.2 % in low-grade serous, 52.2 % in high-grade endometrioid, 35.3 % in low-grade endometrioid, 74.1 % in clear cell and 35.7 % in mucinous tumors. In 2021, the SUR+/CT + -subgroup decreased to 62.9 % versus 69.2 % in 2016. Four-year-disease-free-survival was 86 % for SUR+/CT+, 78 % for SUR-/CT+, 68 % for SUR+/CT- and 57 % for SUR-/CT- (p < 0.001). - Conclusions - One therapy modality cannot replace another one. Although urgently required, quality of therapy has not improved in 2021.
Online veröffentlicht: 15. Februar 2025, Artikelversion: 5. März 2025
Gesehen am 18.08.2025